2019
DOI: 10.3390/cancers11122043
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor of STAT5 Signaling Overcomes Chemotherapy Resistance in Myeloid Leukemia Cells

Abstract: Signal transducers and activators of transcription 5A and 5B (STAT5A and STAT5B) are crucial downstream effectors of tyrosine kinase oncogenes (TKO) such as BCR-ABL in chronic myeloid leukemia (CML) and FLT3-ITD in acute myeloid leukemia (AML). Both proteins have been shown to promote the resistance of CML cells to tyrosine kinase inhibitors (TKI) such as imatinib mesylate (IM). We recently synthesized and discovered a new inhibitor (17f) with promising antileukemic activity. 17f selectively inhibits STAT5 sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Additionally, STAT3 (and not STAT5B) mutations were identified in multiple peripheral T-cell lymphomas (PTCL), as well as high pY-STAT3 expression, particularly in angioimmunoblastic T-cell lymphoma (AITL) and anaplastic large cell lymphoma (ALCL) patient samples, two different PTCL cancer types [26]. From an inhibition perspective, a derivatized indole was shown to be effective in both chronic myeloid leukemia (CML) and acute myeloid leukemia (AML), as well as aggressive STAT5-N642H tumors [27]. Collectively, these studies shed light on the importance of STAT3/5 in several hematopoietic cancers, potentially offering disease biomarkers and hallmarks across several different indications.…”
Section: Chapter 1: Targeting Stat3/5 In Hematopoietic Cancersmentioning
confidence: 99%
“…Additionally, STAT3 (and not STAT5B) mutations were identified in multiple peripheral T-cell lymphomas (PTCL), as well as high pY-STAT3 expression, particularly in angioimmunoblastic T-cell lymphoma (AITL) and anaplastic large cell lymphoma (ALCL) patient samples, two different PTCL cancer types [26]. From an inhibition perspective, a derivatized indole was shown to be effective in both chronic myeloid leukemia (CML) and acute myeloid leukemia (AML), as well as aggressive STAT5-N642H tumors [27]. Collectively, these studies shed light on the importance of STAT3/5 in several hematopoietic cancers, potentially offering disease biomarkers and hallmarks across several different indications.…”
Section: Chapter 1: Targeting Stat3/5 In Hematopoietic Cancersmentioning
confidence: 99%
“…We showed that 17 f suppressed P−Y‐STAT5 and growth of CML and AML cells [41] . We also demonstrated that 17 f sensitizes leukemic cells that acquired resistance to IM or Ara‐C [42] …”
Section: Introductionmentioning
confidence: 57%
“…We previously showed that 17 f overcomes the resistance of CML and AML cells to IM and Ara‐C [42] . We then ask whether 7 a and 7 a’ had a greater impact than 17 f to overcome the resistance of CML cells to IM.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…inhibitor associated with IM suppresses the growth of IM-resistant CML cells by blocking STAT5B protein expression. 41 Importantly, we showed that ACF-mediated effects on STAT3/ STAT5 occur via a BCR-ABL-independent mechanism. We found that ACF alone neither affects the phosphorylation nor the expression of this TKO in IM-sensitive cells, even though minor, but cell death but also cellular senescence.…”
Section: Discussionmentioning
confidence: 75%